On gg-Separation Axioms in Topological Spaces - Reddy H G, Govardhana; M. Ittanagi, Basavaraj (International Journal of Engineering and Technology, 2018)
Study and investigate a class of separation axiom namely gg-Tk space (k=0, 1, 2), gg-regular and gg-normal space. Meanwhile, some of their properties are obtained.Â